Analyzing the un-accounted gas causes in Indonesian household gas networks using text analytics - Hermanto, Emi Heru; Santosa, Budi (Indonesian Journal of Multidisciplinary Science, 2024)
The development and growth process of domestic gas network in Indonesia is one of the Government's efforts towards National Energy Transformation or  Zero Net Carbon Emissions by 2060. In its development, a number of challenges have been found to be addressed by the parties concerned. One of the major challenges faced in the development of jargas is the presence of unaccounted gas or gas losses, which is an unknown amount of gas, such as, for example, the value of un-acccounted gaseous gas in 2022 in a region reaches an average of -24,55%. The size of the UAG (Un-Accounted Gas) value needs to be known by the parties, so research is carried out using operational data such as a monthly report containing free text with the method of text analytics. Text analytics is used to perform Analysis to find out the factors causing the occurrence of value of UAG in Jargas. The analysis uses a number of Phyton-supported tools, including Anaconda, and Power BI. The data analysis uses 3,584 word strings, with 42 UAG cause variables, then extracted into 60 Tokens or keywords, then performed the analysis on 52 unique tokens, then focused on 19 main tokens. The results of the analysis showed that -24,55% of UAG causes are due to leakage (15,56%), third-party activity (3.52%), un-registered thieves (2,22%), gas-in activity (1,99%), and accuracy of measuring instruments (1,42%).